An investigation into the category “attitude” in english and vietnamese articles warning against childhood epidemics from the perspective of appraisal theory (Đại học Ngoại ngữ, Đại học Đà Nẵng, 2025)
An article is a piece of writing about a particular subject in newspapers or magazines . Nowadays, there are many interesting topics attracting readers in the world. Among them, the articles warning against childhood epidemics (AWEs) have attracted much attention of readers. This study investigates the category “ATTITUDE” in English and Vietnamese articles warning against childhood epidemics from the perspective of Appraisal Theory. The data for analysis in this thesis are 100 samples of AWEs (50 in English and 50 in Vietnamese) are posted onto official electronic newspapers. The methods mainly used in the study are qualitative and quantitative combined approaches which include the descriptive, contrastive analysis methods.The main objective of the study is to discover the category Attitude in AWEs. It is realized by its subcategories-Affect, Judgement and Appreciation in terms of lexical features and variables of each subcategory in terms of semantic features. The findings also aim at suggesting some implications for the teaching and learning English in Vietnam. The findings obtained from the lexical features show that both English articles warning against childhood epidemics (EAWEs) and Vietnamese articles warning against childhood epidemics (VAWEs) tend to use verb phrases to express the people’s feelings and evaluate people’s behavior. In addition, both languages prefer to use adjective phrases to assess the things. However, Vietnamese articles are more interested in using these lexical items. With regard to semantic features, the difference is that EAWEs has a tendency to mainly use the subcategory Affect and Judgement, while VAWEs tends to use more than the subcategory Appreciation. One more different thing is that Vietnamese articles usually use negative evaluations in all of subcategories, on the contratry; English articles still use positive evaluations, especially, in the view of evaluating things.